Medial Orbital Epidermoid Cyst - Valkanov St. (Sciendo, 2017)
Dermoid and epidermoid cysts are among the most common orbital tumors, comprising 3% to 9% of all orbital masses. We report a rare case of upper medial orbital epidermoid cyst of a 2-year-old patient. The patient was complaining of pain in the right eye and infrequent vomiting. The neurological and radiographic examinations showed no pathological findings, only after CT scan was performed a tumor formation was found. After the extirpation a histological examination was performed proving the diagnosis.